2022
DOI: 10.1007/s00018-022-04415-x
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet activates splenic NOD1 and enhances neutrophil recruitment and neutrophil extracellular traps release in the spleen of ApoE-deficient mice

Abstract: In the course of atherogenesis, the spleen plays an important role in the regulation of extramedullary hematopoiesis, and in the control of circulating immune cells, which contributes to plaque progression. Here, we have investigated the role of splenic nucleotide-binding oligomerization domain 1 (NOD1) in the recruitment of circulating immune cells, as well as the involvement of this immune organ in extramedullary hematopoiesis in mice fed on a high-fat high-cholesterol diet (HFD). Under HFD conditions, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…and Kasimetty et al . reported diminished chemotaxis of neutrophils into the spleen of Nod1 knockout mice in high‐fat diet‐induced atherosclerosis, and into the kidneys in ischemic kidney disease respectively [50,51]. This effect of NOD1 on chemotaxis was cell type specific, as monocyte/macrophage recruitment to the spleen was not affected [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Kasimetty et al . reported diminished chemotaxis of neutrophils into the spleen of Nod1 knockout mice in high‐fat diet‐induced atherosclerosis, and into the kidneys in ischemic kidney disease respectively [50,51]. This effect of NOD1 on chemotaxis was cell type specific, as monocyte/macrophage recruitment to the spleen was not affected [50].…”
Section: Discussionmentioning
confidence: 99%
“…reported diminished chemotaxis of neutrophils into the spleen of Nod1 knockout mice in high‐fat diet‐induced atherosclerosis, and into the kidneys in ischemic kidney disease respectively [50,51]. This effect of NOD1 on chemotaxis was cell type specific, as monocyte/macrophage recruitment to the spleen was not affected [50]. Chan et al ., however, showed that the reason for reduced high‐fat diet‐induced neutrophil infiltration in adipose tissue in Nod1 knockout mice likely is a diminished Cxcl1 production, as they did not observe changes in neutrophil chemotaxis towards Cxcl1 in Nod1 ‐depleted neutrophils [52].…”
Section: Discussionmentioning
confidence: 99%
“…43 It is possible that the effects could have been mediated by both T cells and other immune cells or in other tissues such as the spleen. [44][45][46][47][48][49][50] Hence, the absence of Tbet did not prevent the mice from developing obesity but prevented insulin resistance which resembles the phenotype observed in Th2-biased Balbc mice and metabolic healthy humans. [10][11][12] Similarly, deviation to Th2 responses or promoting Th2 biased responses in C57bl/6 mice by administering helminths or products derived from helminths led to improvement in symptoms of diabetes mellitus.…”
Section: Effect Of Immune Bias In Diet-induced Obesitymentioning
confidence: 92%
“…When Tbet, the major transcription factor for the elicitation of Th1‐type immune responses was knocked out in the C57bl/6 background it led to the dissociation of visceral adiposity and insulin resistance 43 . It is possible that the effects could have been mediated by both T cells and other immune cells or in other tissues such as the spleen 44–50 . Hence, the absence of Tbet did not prevent the mice from developing obesity but prevented insulin resistance which resembles the phenotype observed in Th2‐biased Balbc mice and metabolic healthy humans 10–12 .…”
Section: Effect Of Immune Bias In Diet‐induced Obesitymentioning
confidence: 99%
“…Feeding an HFD induces neutrophil recruitment into adipose tissue and increases NET formation ( Moorthy et al, 2016 ; Wang et al, 2018a ). NOD1 in HFD-fed mice drives NETosis, which contributes to the regulation of atherogenesis progression ( Fernández-García et al, 2022 ). In recent years, the gut microbiota was found to be strongly associated with NETosis formation.…”
Section: The Role Of Lifestyle Diet Microbiome Genetics and Environme...mentioning
confidence: 99%